2022
DOI: 10.1111/jnc.15723
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid and blood profiles of transfer RNA fragments show age, sex, and Parkinson's disease‐related changes

Abstract: Transfer RNA fragments (tRFs) have recently been shown to be an important family of small regulatory RNAs with diverse functions. Recent reports have revealed modified tRF blood levels in a number of nervous system conditions including epilepsy, ischemic stroke, and neurodegenerative diseases, but little is known about tRF levels in the cerebrospinal fluid (CSF). To address this issue, we studied age, sex, and

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Hence, the associa-tion between tRFs of mitochondrial origin that carry motifs complementary to those of cholinergic transcripts, resemble the enriched sequence-based motifs to cholinergic transcripts in MT-tRFs from the cerebrospinal fluid (CSF) and blood of donors with Parkinson's disease (PD). 72 These results suggest that the mitochondrial damage in neurodegenerative disorders such as PD and AD relates to the failed regulation of cholinergic targets by CholinotRFs, and potentially to a broader cholinergic and mitochondrial linked defect. Surprisingly, we observed mRNA changes associated with ACh production and cholinergic regulation in the hypothalamus and the STG, although these regions lack cholinergic neurons.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hence, the associa-tion between tRFs of mitochondrial origin that carry motifs complementary to those of cholinergic transcripts, resemble the enriched sequence-based motifs to cholinergic transcripts in MT-tRFs from the cerebrospinal fluid (CSF) and blood of donors with Parkinson's disease (PD). 72 These results suggest that the mitochondrial damage in neurodegenerative disorders such as PD and AD relates to the failed regulation of cholinergic targets by CholinotRFs, and potentially to a broader cholinergic and mitochondrial linked defect. Surprisingly, we observed mRNA changes associated with ACh production and cholinergic regulation in the hypothalamus and the STG, although these regions lack cholinergic neurons.…”
Section: Discussionmentioning
confidence: 92%
“…Additional studies identified MT‐tRFs as key regulators in nuclear‐mitochondrial communication, 71 which is dysfunctional in many neurodegenerative diseases, including AD. Hence, the association between tRFs of mitochondrial origin that carry motifs complementary to those of cholinergic transcripts, resemble the enriched sequence‐based motifs to cholinergic transcripts in MT‐tRFs from the cerebrospinal fluid (CSF) and blood of donors with Parkinson's disease (PD) 72 . These results suggest that the mitochondrial damage in neurodegenerative disorders such as PD and AD relates to the failed regulation of cholinergic targets by CholinotRFs, and potentially to a broader cholinergic and mitochondrial linked defect.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, short RNA-sequencing revealed PD-characteristic patterns in both the CSF and blood. 137 These methods also need to be developed for higher throughput. Whether the slope of aggregation in vitro can separate between early PD and late PD as well as between typical PD and other forms of parkinsonism remains to be determined.…”
Section: Biochemical and Molecular Markersmentioning
confidence: 99%
“…Although the effect of templating of PD‐derived CSF samples has been clearly achieved through exogenously added, recombinant, full‐length aSyn, the nature of the “templating agent,” that is, aSyn itself versus non‐aSyn‐based CSF constituent(s), has remained elusive. Interestingly, short RNA‐sequencing revealed PD‐characteristic patterns in both the CSF and blood 137 . These methods also need to be developed for higher throughput.…”
Section: Current “Diagnostic” Biomarkersmentioning
confidence: 99%
“…It has recently been shown that Shlafen2 specifically protects tRNAs from cleavage within the anticodon loop in T cells to allow rapid proliferation to occur despite high levels of metabolic stress, providing an explanation for why tRFs may not be abundant in whole blood analysis 75 . More recently, Paldor et al, performed a more targeted analysis of the PPMI whole blood samples previously described but restricted to idiopathic PD patients only, along with an existing dataset of post mortem CSF samples collected from PD patients and healthy controls 76 . Using a global analysis of tRF types regardless of origin tRNA this study again highlighted a sex difference, which was more pronounced in CSF than in whole blood, however an age-dependent decline in CNS 3'tRFs was also identified.…”
Section: Parkinson's Diseasementioning
confidence: 99%